Hubungan Kepatuhan Minum Tablet Fe dengan Kejadian Anemia (Hb) pada Remaja Putri Di SMP Negeri 1 Tapen Kabupaten Bondowoso - Putra, Kristiyan Adi; Munir, Zainal; Siam, Wiwin Nur (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
Anemia often occurs in young women because in adolescence there has been rapid growth into the age of puberty including red blood cells will increase. In addition, in young women, menstrual cycles begin to occur that will release blood from the body with a considerable amount. One effort that can be done is to consume Fe tablets.The research design is a quantitative method in the form of Cross Sectional Design. The study was conducted on Class VII Adolescent Girls in Junior High School 1 Tapen - Tapen, Bondowoso in May 2019 with a sample of 33 respondents. The measuring instrument used was a questionnaire sheet which then carried out the Spearman Rho analysis test with a significance level of p≤ 0.05. The results obtained p-value 0.007 (P≤ 0.05). So Ho was rejected and H1 was accepted, so there was a correlation between the Compliance of consumption Fe tablets with the incidence of Anemia in Class VII Adolescent Girls in Junior High School 1 Tapen, Tapen, Bondowoso. There is a need for counseling on the importance of consumption of Fe tablets and collaboration with teachers regarding the consumption of Fe tablets. Keywords: Fe Tablet Consumption, Compliance, Incidence of Anemia